Removal of lead and copper from wastewater using Bael fruit shell as an adsorbent. (2022) - Barkade, Shrikant; Sable, Sunil; Ashtekar, Varsha; Pandit, Vikram
Abstract: Water pollution through toxic heavy metals is a severe environmental problem which affects each living individual. In the present paper, activated carbon is synthesised from waste Bael fruit shell (BS). This BS as an adsorbent is explored for the elimination of Lead (Pb) and Copper (Cu) toxic metals from the solution. Batch process is demonstrated to study the effect of pH, metal ion concentration and adsorbent dosage. Change on the surface morphology as well as the validation of Pb and Cu binding on the adsorbent at various stages were obtained by SEM and FTIR. Phosphoric acid activation played an important role to develop the well-defined pores on adsorbent surface. Herein, the results shows that the Bael Fruit Shell Activated Carbon (BSAC) is an effective and economical viable adsorbent for Pb and Cu removal from water. Composite materials of nano, polymer with present adsorbent (BSAC) can be utilize for removal of other toxic metals as well as for the removal of complex organic dyes from waste water.